U-Th-Pb geochronology and simultaneous analysis of multiple isotope systems in geological samples by LA-MC-ICP-MS - Xie, L.; Evans, Noreen; Yang, Y.; Huang, C.; Yang, J. (Royal Society of Chemistry, 2018)
Laser ablation single/multiple collector inductively coupled plasma mass spectrometry (LA-SC/MC-ICP-MS) has become one of the most widely used in situ micro-analytical tools for the determination of isotopic ratios and trace element signatures in solid geological materials. The advantages include high spatial resolution, high sample throughput, good precision and accuracy, and limited sample preparation. For the application of these techniques in U-Th-Pb geochronology, the main challenges involve ion counter drift, matrix differences between reference materials and samples, laser-induced downhole elemental fractionation and common lead corrections. Given the requirement to achieve the maximum amount of geochemical information within the limited analytical domain of complexly zoned or small samples, simultaneous analysis of multiple isotopic systems and/or trace elements using laser ablation split stream (LASS) techniques is now widely applied. This article summarizes recent advances in LA-SC/MC-ICP-MS U-Th-Pb geochronology and LASS techniques. We review recent efforts to improve spatial resolution, calibrate ion counter drift, and correct for common lead contamination, elemental fractionation and matrix mismatching. A summary of the range of minerals utilized for LA-MC-ICP-MS geochronology and LASS is provided, along with a discussion of potential directions for future research.